2021
DOI: 10.1037/apl0000837
|View full text |Cite
|
Sign up to set email alerts
|

Does CWB repair negative affective states, or generate them? Examining the moderating role of trait empathy.

Abstract: Counterproductive work behavior (CWB) is a topic of considerable importance for organizational scholars and practitioners. Yet, despite a wide-ranging consensus that negative affect (NA) is a precursor to CWB, there is surprisingly little consensus as to whether CWB enactment will subsequently lead to lower or higher levels of NA. That is, scholars disagree as to whether CWB has a reparative (negative) or generative (positive) effect on subsequent NA. We submit that both perspectives have validity, and thus th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 151 publications
(232 reference statements)
2
24
0
Order By: Relevance
“…Furthermore, common method bias is less of a concern when testing interaction effects (Podsakoff et al, 2012; Siemsen et al, 2010). With regard to low base rates, our low means are consistent with prior research investigating deviant behavior (e.g., Koopman et al, 2020) and technology transfer-related behavior in general (Huyghe et al, 2016). That said, future research should consider obtaining information from multiple sources such as department heads and deans, as well as objective data on technology transfer behavior (e.g., meetings with the TTO, patents filed, spin-offs created, court disputes).…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, common method bias is less of a concern when testing interaction effects (Podsakoff et al, 2012; Siemsen et al, 2010). With regard to low base rates, our low means are consistent with prior research investigating deviant behavior (e.g., Koopman et al, 2020) and technology transfer-related behavior in general (Huyghe et al, 2016). That said, future research should consider obtaining information from multiple sources such as department heads and deans, as well as objective data on technology transfer behavior (e.g., meetings with the TTO, patents filed, spin-offs created, court disputes).…”
Section: Discussionsupporting
confidence: 87%
“…Thus, Hypothesis 2 was partially supported. 345 To assess the practical relevance of our predictors, we calculated the R 2 using model likelihood statistics for our supported paths, following the method of Lang et al (2019) and the recent examples of Anicich et al (2020) and Koopman et al (2020). We found that the best possible leader self explained 1.3% of the variance in positive affect, positive affect explained 2.3% of the variance in helping and 3.1% of the variance in visioning, helping explained 3.3% of the variance in enacted leader identity, and visioning explained 5.2% of the variance in enacted leader identity and 3.8% of the variance in clout.…”
Section: Resultsmentioning
confidence: 99%
“…A recent paper from Koopman et al. (2020) also provides a potential lens through which to view time theft. That is, time theft could be seen as a form of cathartic behavior.…”
Section: Discussionmentioning
confidence: 99%